Consumer Bankruptcy Regimes In Europe - Tamás Fézer; Nikolett Zoványi (Universitas Islam Indonesia, 2023)
Consumer over-indebtedness has been a problem in Europe especially since the 2008 financial crisis. Legal procedures addressing consumer insolvency were scarce and sporadic prior to 2008, however, legislation have accelerated in most Member States of the European Union in the past fifteen years. In lack of any harmonization in the area of consumer bankruptcy in the EU, Member States, while learning from each other in some instances, established their own procedures and regulatory frameworks. The paper attempts to map the various approaches in addressing consumer over-indebtedness looking for common cores to serve as a base for a future legislation in an EU level. The research follows a comparative method mostly relying on the analysis of the relevant norms in the Member States of the EU also wandering to the territory of the sociology of law. The paper concludes the consumer bankruptcy regimes in Europe can be categorized easily and show similarities mostly in the identification of the vulnerable groups and in the legal consequences of the procedures. This finding proves there is ground for the European Commission to propose legislation, preferably in the form of a directive of the Council and of the European Parliament, to ensure a harmonized approach in the field of consumer bankruptcy procedures.Keywords: Consumer bankruptcy, consumer law, European Union law, insolvency. Rezim Kebangkrutan Konsumen Di Eropa AbstrakUtang berlebih konsumen telah menjadi masalah di Eropa terutama sejak krisis keuangan 2008. Prosedur hukum yang menangani kebangkrutan konsumen langka dan sporadis sebelum tahun 2008, namun, undang-undang telah dipercepat di sebagian besar Negara Anggota Uni Eropa dalam lima belas tahun terakhir. Karena kurangnya harmonisasi di bidang kebangkrutan konsumen di UE, Negara-negara Anggota, sambil belajar dari satu sama lain dalam beberapa kasus, menetapkan prosedur dan kerangka peraturan mereka sendiri. Makalah ini mencoba untuk memetakan berbagai pendekatan dalam menangani konsumen yang terlilit hutang yang mencari inti umum untuk menjadi dasar undang-undang masa depan di tingkat UE. Penelitian mengikuti metode komparatif yang sebagian besar mengandalkan analisis norma-norma yang relevan di Negara-negara Anggota UE yang juga mengembara ke wilayah sosiologi hukum. Makalah ini menyimpulkan rezim kebangkrutan konsumen di Eropa dapat dikategorikan dengan mudah dan menunjukkan kesamaan sebagian besar dalam identifikasi kelompok rentan dan konsekuensi hukum dari prosedur tersebut. Temuan ini membuktikan adanya dasar bagi Komisi Eropa untuk mengusulkan undang-undang, sebaiknya dalam bentuk arahan dari Dewan dan Parlemen Eropa, untuk memastikan pendekatan yang harmonis di bidang prosedur kebangkrutan konsumen.Kata kunci: Kebangkrutan konsumen, hukum konsumen, hukum Uni Eropa, kebangkrutan.